Supraorbital Nerve and Cavernous Sinus Invasion with Poorly Differentiated Carcinoma of Unknown Primary. (3rd September 2018) - Patel, Saagar N.; Nakawah, Mohammad Obadah; Sadaka, Ama; Berry, Shauna; Ortiz Gomez, Juan; Powell, Suzanne; Lee, Andrew G.
ABSTRACT: A 50-year-old man presented with a 4-month history of right-sided trigeminal neuropathy in the V1 and V2 distribution, right sixth nerve palsy and Horner syndrome. Magnetic resonance imaging (MRI) showed enhancement and thickening along the right ophthalmic nerve and supraorbital nerve and fullness at the right cavernous sinus extending to Meckel's cave. Evaluation for a primary tumour was negative. Cavernous sinus biopsy showed infiltrating poorly differentiated carcinoma; the patient underwent radiation therapy. To our knowledge this is the only case of poorly differentiated carcinoma involving the supraorbital nerve presenting with trigeminal neuropathy and Horner syndrome in the English ophthalmic literature.